Achilles tendon rupture: etiology, diagnosis, prevention, repair, complications and their relation to future sports performance in the athletic population - Skorupska, Marta; Czeczotka, Magdalena Joanna; Martka, Martyna Magdalena; Popławska, Natalia Aleksandra; Śliz, Justyna; Woźniak, Krzysztof (Quality in Sport, 2024)
The Achilles tendon is the most powerful and longest in our body. 20% of all serious tendon ruptures involve the Achilles tendon (AT). An AT rupture can be a career-ending injury. Proven risk factors predisposing and preventing tendon rupture are presented, as well as epidemiological data on the incidence of this disease in the population. In addition, it illustrates currently used diagnostic methods and presents the benefits they bring. Achilles tendon ruptures have a detrimental impact on athletic performance, and the most appropriate treatment method and return-to-play recommendations remain controversial. Recent studies show that operative intervention improves strength and functional results and is more effective compared to non-operative treatment combined with rehabilitation. Currently, according to the latest research, surgical intervention should be used, especially in athletes and very physically active people, because it shortens the time to return to full fitness and allows for better sports achievements in the future. However, you should remember about the complications that may result from such treatment. Nevertheless, the benefits of surgery outweigh the possible losses, especially to the athletic population. The purpose of this study is to comprehensively review the relationship between surgical repair of a ruptured AT and future athletic performance in an athlete population. The available research shows the effectiveness, side effects, complications, and benefits of surgical correction of a ruptured tendon in the athlete population, as well as the quality of performance they are able to achieve after recovery. Materials and methods: Materials used in this study were found in the PubMed database, using the following keywords: Achilles tendon”, Achilles tendon rupture”, Return to play’’, Athletes injury”, Athletic population”.